Sistem Pendukung Keputusan Penentuan Hotel Terbaik Dikota Medan Menerapkan Metode Multi Objective Optimization on The Basis of Ratio Analysis (MOORA) - Putra Heri; Mesran (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Medan City is the city with the number 4 highest population rank in Indonesia. This makes developments in terms of tourism, shopping centers, hotels, so fast. In the field of hospitality there are several 5, 3 or below star hotels with a variety of advantages and facilities offered to make it, both communities around Medan, or those outside the city area. Medan is confused to choose which hotel is the best and is good for staying and relaxing. Criteria for prices, facilities and types of rooms offered by several hotels are a guideline for the community to choose which hotel is the best. But with dozens of hotels available, this makes it difficult for consumers to determine a decision on the best hotel in the city of Medan. Based on the considerations above, researchers are interested in conducting research in determining the Best Hotels in the city of Medan by using the Multi-Objective Optimization method on The Base Of Ratio Analysis (MOORA) so as to solve the problems faced by the people of Medan or outside the city of Medan